Síntese de 7-trifluormetil-5,6-diidrobenzo[c]acridinas - Drekener, Roberta Lopes (2005)
This work describes the reactions of 1-methoxy-2-trifluoroacetyl-3,4-dihydro-naphthalene (4) with substituted anilines 5a-j to obtain a series of N-aril-2-trifluoroacetyl-3,4-diidronaphtalenes (6a-j). Intramolecular cyclization of 6a-j furnished a novel series of substituted 7-trifluoromethyl-5,6-dihydrobenzo[c]acridines (7a-j). Coumpond 4 was obtained from the trifluoroacetylation reaction of the mixture of acetal (2) and enoléter (3) derived from ketone α-tetralone (1) with trifluoroacetic anhydride. The reactions of 1-methoxy-2-trifluoroacetyl-3,4-dihydro-naphthalene (4) with anilines 5a-j, in molar ratio 1:1, were carried out in acetonitrile at 81oC for 6 hours leading to the compounds 6a-j in 68-87%. The synthesis of 7-trifluoromethyl-5,6-dihydrobenzo[c]acridines (7a-j) were carried out by intramolecular cyclization reaction of 6a-j in the presence of polyphosphoric acid (PPA), in abscence of organic solvent at 110oC for 24 hours, in 44-82%. Others Lewis acid such as TiCl4, ZnCl2, P2O5/POCl3, POCl3 or CF3COOH and triethylamine were employed to obtain 7a, however only the reactions using PPA gave positive results.